2019
DOI: 10.1002/bit.26931
|View full text |Cite
|
Sign up to set email alerts
|

Construction of mini‐chemostats for high‐throughput strain characterization

Abstract: To achieve large‐scale, high‐throughput experiments for systems biology research of microorganisms, reliable data from robust cultivation systems are needed. Chemostats are such systems, ensuring reproducibility and quality by providing a stable, well‐controlled environment for the cells. However, many of the available chemostat systems require large amounts of media and are complex to set up and expensive to purchase and maintain. To address these concerns, we developed a mini‐chemostat (MC) system with 16 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…The for continuous cultivations modified single-use stirred-tank bioreactor system (bioREACTOR, 2mag AG) operates with eight parallel reactors at a working volume of 10 mL [26]. The mini-chemostat (MC) system developed by Bergenholm et al [27] comprises 16 parallel reactors and requires a working volume of 40 mL. Our system is therefore well applicable for the simple and cost-effective screening of microbial performance in continuous mode.…”
Section: Resultsmentioning
confidence: 99%
“…The for continuous cultivations modified single-use stirred-tank bioreactor system (bioREACTOR, 2mag AG) operates with eight parallel reactors at a working volume of 10 mL [26]. The mini-chemostat (MC) system developed by Bergenholm et al [27] comprises 16 parallel reactors and requires a working volume of 40 mL. Our system is therefore well applicable for the simple and cost-effective screening of microbial performance in continuous mode.…”
Section: Resultsmentioning
confidence: 99%
“…A membrane-based fed-batch shake flask with a Respiration activity monitoring system (RAMOS) device was also used to study the effect of substrate-limited fed-batch conditions (Habicher et al, 2019b). A mini-chemostat (MC) system (16 reactors with 40 ml working volume) was developed to characterize yeast physiology, and it was shown that the MC system provided the same environmental conditions as the DASGIP R parallel bioreactor system (Eppendorf) (Bergenholm et al, 2019). In a recent review, a systematic approach toward scale-down model (SDM) development in ambr 15 systems was described, and it was suggested that ambr SDMs are suitable for future regulatory submissions (Sandner et al, 2018).…”
Section: High-throughput Cultivation Systemsmentioning
confidence: 99%
“…This can be partially achieved using continuous culture devices such as a turbidostat, which dilutes cells during growth to maintain a constant optical density (OD). In recent years, a number of turbidostat platforms have been developed and are beginning to find widespread applications in systems, synthetic, and evolutionary biology [11][12][13][14][15][16][17][18][19]. There has also been significant development of open-source platforms for optogenetics [20,21], which have been used to implement real-time measurement [22] and feedback control [23] and to demonstrate orthogonal regulation of multiplexed optogenetic regulators [24].…”
Section: Introductionmentioning
confidence: 99%